EFEKTIVITAS PENDEKATAN KONSTRUKTIVISTIK BERDASARKAN INTEGRASI DIMENSI MSSM PADA PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR KIMIA SISWA - Bekti Mulatsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
This study aims to determine whether there is a significant difference in understanding the concept and motivation of chemistry learning among students of class XI MIPA SMA Negeri 1 Banguntapan in 2014/2015 academic year that attended the constructivistic approach learning procces with and without the integration of macroscopic dimensions, symbolic dimensions, and submicroscopic dimensions. The initial knowledge of chemistry is statistically controlled. This study was an experimental research with one factor, two sample, and one covariable research design and one factor two sample research design. The population of this study were 128 students of Class XI MIPA SMA Negeri 1 Banguntapan that were divided into 4 classes. The sample in this study were 64 students taken by purposive sampling and divided into two classes, namely experiment class (A1) with 32 samples and control class (A2) with 32 samples. The data obtained in this study were early chemistry knowledge data, early and final chemistry study motivation, and student’s understanding data of chemistry concept. The hypothesis was analyzed with anakova (covariance analysis) and t-test. The results showed that there were no significant differences in understanding the concept and motivation of chemistry learning at class XI MIPA in SMA Negeri 1 Banguntapan that attended the learning procces with constructivistic approach based on the integration of macroscopic dimensions, symbolic dimensions, and dimensions submicroscopic and who follow the learning with constructivist approach without macroscopic dimension integration, symbolic dimensions, and submicroscopic dimensions. The implementation of constructivist approach based on dimension integration in chemistry is not effective in understanding the concept and motivation of chemistry learning in class XI MIPA of SMA Negeri 1 Banguntapan at 2014/2015 academic year.